Using Piezoelectric System in Oral and Maxillofacial Surgery (International Journal of Medical and Surgical Sciences, 2015)
Motors and handpieces with the piezoelectric system have recently been used in several surgeries, following the current minimally invasive trend surgery. The system consists of crystals or ceramics undergoing deformation when exposed to electrical current, resulting in an oscillating movement with ultrasound frequency. In the Oral and Maxillofacial Surgery field activity, the piezosurgery may be used in maxillary and mandibular osteotomies in the orthognathic surgery, alveolar corticotomies, cysts tumors, facial trauma surgery, among others. This study aims to present a literary review on the piezoelectric system, which allows discussion to their use and effectiveness in oral surgery procedures.
Keywords: Oral Surgery; Orthognathic Surgery; Osteotomy; Piezosurgery